STC2 promotes anoikis resistance by modulating TGIF1 mRNA stability in colorectal cancer - Hu, Fan; He, Qiuming; Ding, Zheyu; Cheng, Jie; Lin, Jun (Frontiers in Cell and Developmental Biology, 2026)
BackgroundStanniocalcin-2 (STC2), a glycosylated protein originally identified in the endocrine glands of fish, plays multiple biological roles in cancer. However, its functional significance and molecular mechanisms in colorectal cancer (CRC) remain unclear.MethodsBioinformatic analyses and CRC tissue specimens were used to determine STC2 expression and its prognostic value. The biological effects of STC2 on CRC cells were assessed using flow cytometry and live/dead staining assays. The underlying mechanisms were further explored by RNA sequencing, RNA immunoprecipitation (RIP), and RNA stability assays.ResultsSTC2 was significantly upregulated in CRC tissues and cell lines, and its high expression was associated with poor prognosis in CRC patients. Functional experiments demonstrated that STC2 enhanced CRC cell resistance to anoikis by upregulating TGIF1 expression. Mechanistically, STC2 bound to TGIF1 mRNA and stabilized it by inhibiting its degradation.ConclusionOur findings suggest that STC2 promotes anoikis resistance in CRC by regulating TGIF1 mRNA stability. STC2 may serve as a potential therapeutic target and prognostic biomarker for colorectal cancer.